2016
DOI: 10.3402/ejpt.v7.30995
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-year follow-up of childhood avalanche survivors

Abstract: BackgroundEvery year a substantial number of children are affected by natural disasters worldwide. However, data are scarce on long-term psychological impact of natural disasters on children's health. Identifying risk factors and outcomes associated with the long-term sequelae of posttraumatic stress disorder (PTSD) can provide a gateway to recovery as well as enhancement of preventive measures.ObjectiveAmong childhood avalanche survivors, we aimed to investigate risk factors for PTSD symptoms and the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
3
17
1
1
Order By: Relevance
“…parents with symptoms of psychological morbidity reported same prevalence of symptoms among their children as other parents (although heightened but not significant for anxiety or worries and headache(s)). This is not in line with our previous study on childhood avalanche survivors, which found that traumatic reactions of caregivers in the aftermath of the disaster predicted PTSD symptoms among childhood survivors 16 years post-trauma (Thordardottir et al, 2016). In addition, a recent meta-analysis of the association between parental PTSD and/or depressive symptoms and PTSD symptoms in children after exposure to a traumatic event, also confirmed this association (Morris, Gabert-Quillen, & Delahanty, 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…parents with symptoms of psychological morbidity reported same prevalence of symptoms among their children as other parents (although heightened but not significant for anxiety or worries and headache(s)). This is not in line with our previous study on childhood avalanche survivors, which found that traumatic reactions of caregivers in the aftermath of the disaster predicted PTSD symptoms among childhood survivors 16 years post-trauma (Thordardottir et al, 2016). In addition, a recent meta-analysis of the association between parental PTSD and/or depressive symptoms and PTSD symptoms in children after exposure to a traumatic event, also confirmed this association (Morris, Gabert-Quillen, & Delahanty, 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…We have increasingly acknowledged the needs of children in the aftermath of disasters (see, e.g., special issue Dyregrov, Yule, & Olff, 2018). Furthermore, long-term studies have established that an experience of a disaster can become a psychological burden that endures for decades (Arnberg, Hultman, Michel, & Lundin, 2013;Bakic & Ajdukovic, 2019;Thordardottir et al, 2016;Zaetta, Santonastaso, & Favaro, 2011).…”
Section: Mass Trauma and Early Interventionsmentioning
confidence: 99%
“…Responses to trauma differ widely, from being resilient (Southwick, Bonanno, Masten, Panter-Brick, & Yehuda, 2014), to quickly recovering while for a subgroup of individuals, posttraumatic stress symptoms (PTSS) may persist for years (Smid, Van Der Velden, Gersons, & Kleber, 2012). From a clinical point of view, it is important to understand how PTSS develops over time and which factors are predictive for the different development patterns (Thordardottir et al, 2016). An increasing number of studies have used…”
Section: Trajectories Of Ptss the Issue Of Limited Data And A Bayesmentioning
confidence: 99%